HUBUNGAN PENGETAHUAN, SIKAP, DAN MASA KERJA DENGAN PERILAKU PETUGAS KESEHATAN DALAM PENGELOLAAN LIMBAH MEDIS DI PUSKESMAS - Novi Ulandari; Yulis Marita (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2023)
Health Center play an important role in public health service, and its activities health center can contribute on medical waste non medical waste,it can be in form of solid, liquid, and gas. The aim of this research is to determine the correlation between knowledge, attitude, and years of service with the bahavior of health works. Methods of this research is cross sectional method. The sampel of this research is the whole health workers at sukaraya health center totaling 88 people. Data analisis used is univariate and bivariate with the chi- square statistical test. Based on univariate analysis, the results obtained from 88 respondents, there were 66 (75%) with good behavior, there were 58 (65,9%) health workers with good knowledge, there were 65 (73,9%) health workers with a positive attitude,there were 75 (85,2%) health workers with years of service ≥ 5 year. Based on bivariate analisis it shows that there is a significant relationship between knowledge and behavior of health workers in medical waste management with a p value 0,038 < 0,05 , there is a significant relationship between attitudes and behavior of officers in medical waste management with p value 0,036 < 0,05 and there is no significant relationship between length of service and staff behavior in medical waste management with p value 0,297 > 0,05. The conclusion of the research is there is a significant relationship between knowledge and attitudes with behavior of health workers in managing medical waste and there is no significant relationship between length of service and behavior of health workers in management of medical waste.